FRAME DAN PERSPEKTIF MASJID JOGOKARIYAN PADA ULASAN GOOGLE MAPS; KAJIAN LINGUISTIK KORPUS - Hidayat, Rahmat; Roselani, Ni Gusti Ayu (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The Jogokariyan Mosque is a religious tourism location in Yogyakarta. Many people already know the Jogokariyan mosque both from Yogyakarta residents and outside Yogyakarta. Some visitors have different views about the Jogokariyan mosque. The difference can be seen from the linguistic expressions of visitors, both from direct interviews, netizens' comments on social media and reviews on Google Maps. The opinions of visitors on the Google Maps application of the Jogokariyan Mosque show individual thoughts on the mosque. This research aims to find out the thoughts of visitors to the Jogokariyan Mosque, especially from the point of view of google maps review. The research data is in the form of visitor reviews, which are collected through transcription techniques. The collected data were analyzed in two stages, first, classified using a corpus linguistic approach using Antconc_64bit software, second, analyzed using a cognitive linguistic approach, Frame theory and Fillmore Perspective. The results of the study showed 100 keywords classified based on word rank and word similarity. The next results show that the keyword "management" is the center of the reviewer's perspective that the author maps in two parts, namely financial management and human resource management. The two mapping results show that the dominant viewpoint of visitors towards the Jogokariyan mosque is a mosque with good financial management and human resource management. The data is presented in formal form, namely using tables and charts, and in informal form, namely using ordinary language explanations. Keywords: frame and perspective, Jogokariyan Mosque, google maps review, corpus linguistics, cognitive linguistics